Selective Borylation of [4]Helicene. Issue 34 (27th October 2016) - Nečas, David; Kaiser, Reinhard P.; Ulč, Jan
Abstract : The Ir‐catalyzed borylation of [4]helicene under different reaction conditions was studied for the first time. The results indicate that monoborylation proceeds to give a mixture of 2‐ and 3‐borylated products in good yields (up to 74 % isolated yield). It was possible to shift the selectivity in favor of the 3‐borylated product by using sterically demanding ligands. The monoborylated [4]helicenes were further arylated by using a Suzuki–Miyaura cross‐coupling or oxidized to the corresponding phenols in very good yields. Abstract : The Ir‐catalyzed borylation of [4]helicene has been studied. The monoborylation proceeds to give a mixture of 2‐ and 3‐borylated products in good yields. The use of sterically demanding ligands favors the formation of the 3‐borylated product. The monoborylated [4]helicenes were arylated by using a Suzuki–Miyaura cross‐coupling reaction or oxidized to the corresponding phenols in very good yields.